THE POSSIBILITIES OF LIFELONG LEARNING IN THE PROFESSIONAL EDUCATION: THE ASSESSMENT OF THE CONTENT OF PROFESSIONAL SECONDARY EDUCATION - Zalaiskalne, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the article is to evaluate the content of professional secondary education programs from the point of life-long education pedagogic aspect. Evaluation of professional secondary education program content is based on the pedagogic statements of life-long education and data of researched performed by the author. Analysis and interpretation of research results is the basis for conclusions about the realization of life-long education principles in the level of professional education program. Main conclusions: the element of professional education program such as lessons of own-initiative work is one of instruments for the realization of life-long education principles, which currently is not completely used; there is a lack of methodological argument about particular elements of the content such as lessons of own-initiative work or inclusion of the amount of content parts in programs; mutual cooperation between teachers of educational institutions and representatives of state institutions promotes development of more qualitative content of professional secondary education.